Islamic Philanthropy: The Idea of Economis Empowerment of the Ummah of K.H. Ma’ruf Amin - Muhammad Alwi; M. Ilham; Muhammad Fakhri Amir (IAIN Padangsidimpuan, 2021)
This article describes the portrait of the Islamic Philanthropy idea of KH. Ma'ruf Amin in the context of the economic empowerment of the Ummah. This paper rests on the basic premise that religion cannot be separated from the social dynamics of society. Methodologically, this article is library research using analytical descriptive method and normative, historical, and sociological approaches as a reading instrument for various literatures. In the context of Islamic philanthropy, the idea of economic empowerment of K.H. Ma'ruf Amin pivots on strengthening regional economic infrastructure and equitable development. Inequality of the economy of Indonesia is the result of past economic policies that adopted the conglomeration model of the trickle-down effect theory. To respond to this model, K.H. Ma'ruf Amin offers a pattern of economic development that adopts the ketupat model, which describes an increase in the economy in the weak economic sector so that there is a gradual increase in the middle economic sector